Impact of conventional managemental practices on reproductive performance of rural buffaloes - BRAR, P S; NANDA, A S (The Indian Journal of Animal Reproduction, 2023)
Data on reproduction vis-a-vis management of 850 rural buffaloes in various agro-eco zones of Punjab revealed that round the year green fodder deficiency prevailed in each zone and animals were fed with variable quantities of wheat/rice straw and concentrates. Prepartum supplementary feeding was prevalent more in Southern Punjab and least in Central Punjab. While wallowing was practiced widely in Southern Punjab, buffaloes were given bath l - 3 times daily in Central Punjab to ward off summer heat. " Doka", the post milking engorgement of teats was a much relied upon sign of ensuing oestrus in each zone, especially so in nomadic herds. While variable incidence of anoestrus was recorded round the year and in each zone, it was highest in nomadic herds during summer. A critical analysis revealed that prepartum supplemented buffaloes had early onset of postpartum ovarian activity and fertility. Further, higher proportion of buffaloes exposed to wallowing had overt signs of oestrus. It is concluded that area - based managemental traditions have a bearing on buffalo reproduction and that fertility can be improved through improvised management and feeding practices.